Research Issues in Attempting to Support an Architecture Firm Transition from Fragmented CAD to BIM Collaborative Design - Forgues, Daniel; Lapalme, James (Cooperative Design, Visualization, and Engineering, 2017)
Research emphasizes the importance of BIM use to be collaborative in order to reap its benefits. However, little research has been conducted regarding the impact at the organizational level of breaking boundaries between specialties for a more collaborative approach to design using BIM. The originality of this longitudinal research is to present not only the challenges of an architecture firm in adopting a multidisciplinary collaborative design, but also the challenges of a Construction Engineering approach to research. Various research strategies derived from activity theory and cognitive sciences were used more or less successfully to accelerate the transition from fragmented to integrated design practices.